The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/147323001003800405
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prenatal Counselling on Postpartum Contraceptive Choice

Abstract: This study tested the hypothesis that individual counselling in the third trimester would increase postpartum contraceptive use to a greater extent than only providing an educational leaflet. A total of 180 third trimester pregnant women of mean age 28.3 years who were attending Marmara University Hospital for prenatal care were enrolled. One-third were randomly allocated to receive prenatal contraceptive counselling and the remaining two-thirds (control group) received an educational leaflet. Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 10 publications
4
48
0
1
Order By: Relevance
“…Educational interventions included 1 or more counseling sessions about contraception and/or breastfeeding during the prepartum period [2631], on the postpartum ward [3235], or during the later postpartum period in the clinic [30,32]. The studies varied in the duration of follow-up, which ranged from 6 weeks to 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Educational interventions included 1 or more counseling sessions about contraception and/or breastfeeding during the prepartum period [2631], on the postpartum ward [3235], or during the later postpartum period in the clinic [30,32]. The studies varied in the duration of follow-up, which ranged from 6 weeks to 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies [2635] evaluating educational interventions, 5 studies [27,3032,34] of poor to good quality showed an improvement in contraceptive use, and 2 showed a decrease in repeat pregnancy within 12 months [30] or 9 months [27]. In a randomized controlled trial conducted in Pakistan [34], the intervention group received a 20-minute counseling session along with a 1-page leaflet after delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that initiation of contraception during the postpartum visit may be facilitated through closer hospital-outpatient linkages 19,20 and clinic protocols that repeatedly inform women about contraceptive options in their postpartum period. [21][22][23] Clinic protocols also should facilitate the use of any medical visit during the postpartum period to counsel and dispense contraception, even if the primary reason for the clinic visit was not family planning and including visits to the pediatrician for the infant. Family planning settings should be encouraged to schedule combined appointments for mother and infant so that the contraceptive discussion is a part of the infant-visit checklist each time in the first 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…38,40 The effectiveness of counseling interventions in reducing unintended pregnancy and increasing postpartum contraceptive use, however, has been seldom examined. 39,43 Of those studies investigating the topic, several have concluded that focused contraceptive counseling in the postpartum or antepartum period is effective, [45][46][47] yet others report no impact on contraceptive use following contraception counseling 48 alone, versus educational leaflets, 49 or a short-term increase in contraceptive use only. 40 A systematic review (2010) of contraceptive counseling interventions taking place in the postpartum period, including both short-term and multiplecontact interventions, concluded that postpartum contraceptive education led to more contraception use and fewer unplanned pregnancies, though, was based on a limited number of studies.…”
Section: Postpartum Contraception Education For Patients; When To Stamentioning
confidence: 99%